A 4D feature-tracking algorithm : a multidimensional view of cyclone systems - Lakkis, Susan Gabriela (2018)
Fil: Lakkis, Susan Gabriela. Pontificia Universidad Católica Argentina, Facultad de Ingeniería y Ciencias Agrarias; Argentina